Jaringan Kolaboratif Digital Untuk Pemasaran Kopi Berbasis Lembaga Masyarakat Desa Hutan (LMDH) Dan Green Economy - Amanna Dzikrillah Lazuardini; Pathmi Noerhatini; Gilang Aditya Pratama (Jurnal Sosioteknologi, 2023)
The digital transformation changes the way work is handled by using information technology to gain efficiency and effectiveness. It also includes the adoption and integration of new information and communication technologies for the completion of sustainable solutions. This process also involves new organizational forms and new business models. Digital transformation requires a digital collaborative network (Digital Collaborative Network, or DCN) among stakeholders in the 4th industrial revolution. The purpose of forming this collaborative network is to balance competition and share information, which will bring many benefits to the collaborating parties. The main objective of this program is to create a DCN for coffee marketing based on existing data at Tenjolaya’s LMDH (Forest-Village Community). The goal is to form a digital community with three main networks, namely ICT networks, knowledge networks, and social networks. Another goal is to train LMDH members to use ICT innovation and LMDH assistance so that they are ready to become a digital community. The target activities include four things: (1) mapping and socializing the DCN concept; (2) producing and processing development activities; (3) increasing the ability of farmer groups to be digital communities (through training and mentoring); and (4) conducting commercial activities.